The Influence of Digital Knowledge Exchange on Advancing Irish Students Knowledge and Adoption of Sustainable Grassland Management Innovations - Martin Mulkerrins; Robert Strong; John Kilboyle; Catherine Egan; Conor Holohan; Tomás Russell; Sinéad Flannery; Edna Curley (Journal of International Agricultural and Extension Education, 2025)
Ireland’s researchers and agricultural advisors emphasize good grassland management as a hallmark of good farming. Formal structured agricultural education and training is a major model of agricultural extension that helps farmers become more innovative and adaptable. Our purpose was to explore the perspectives of Irish higher-level agricultural science and agri-business students who engaged in virtual discussion groups. We employed a co-facilitation approach to help students bridge the gap between theory and practical application in grassland management. Participants were undergraduate students enrolled in two Bachelor of Sciences programs. Third and fourth-year students (n=182) had the opportunity to join non-credit virtual discussion groups focusing on grass measuring and budgeting. Of the 59 expressions of interest, three discussion groups were formed: dairy, dairy and drystock, and drystock only. Group assignments were based on student motivations, farm interests, and grass measuring experience, ensuring the program was tailored to support student learning and innovation. The groups were designed to facilitate learning and behavior change around best practices in grassland management. Participants acknowledged the value associated with opportunities to collaborate with peers as well as experts in the field in terms of developing their knowledge and skillsets with respect to grassland management. Evidence of behavior change regarding grassland management practices at farm level are presented which suggests virtual discussion groups can support increased adoption of (complex) grassland innovations. Recommendations for future delivery are discussed.
Keywords: Extension; Education; Adoption; Sustainability; Digital; Agricultural Innovations; Grassland Management